THE INFLUENCE OF EMPLOYMENT SOCIAL SECURITY ON CUSTOMER SATISFACTION AT BPJS EMPLOYMENT MEULABOH BRANCH, WEST ACEH DISTRICT - Nurjadidah; Fakhrurradhi Luthfi; Rismawati; Marniati; Teungku Nih Farisni (PT. Radja Intercontinental Publishing, 2024)
The Meulaboh Branch Employment Social Security Organizing Agency is a public program that provides protection to workers to overcome certain socio-economic risks and is implemented using a social insurance mechanism. The problem that often occurs with this company is that the existing social security program has not been able to provide welfare to customers when their claims are received. The aim of this research is to determine the influence of the relationship between the employment social security program and customer satisfaction at BPJS Employment Meulaboh Branch. The method used in this research is univariate analysis which aims to obtain frequency distribution data for each variable, then the data is presented in the form of a frequency distribution table. Meanwhile, this analysis method is used to determine the hypothesis by determining the relationship between the independent variable (independent variable) and the dependent variable (dependent variable) using the Chi-square (X2) SPSS version 26 statistical test with a confidence level/CI of 95% and α = 0.05. Based on the research results, it shows that there is a relationship between the work accident insurance program and BPJS Employment customer satisfaction (Pvalue = 0.001 < α = 0.05, RP = 2.103). There is a relationship between the death insurance program and BPJS Employment customer satisfaction (Pvalue = 0.004 < α = 0.05, RP = 1.981). There is a relationship between the old age insurance program and BPJS Employment customer satisfaction (Pvalue = 0.033 < α = 0.05, RP = 1.646). There is a relationship between the pension guarantee program and BPJS Employment customer satisfaction (Pvalue = 0.000 < α = 0.05, RP = 3.951).